A Focussed Literature Review of Power and Influence Leadership Theories - Richard Olley (ACHSM, 2021)
This Narrative Theoretical Literature Review relates to the evolution and translation of two contemporary leadership theories and anchors these to a leadership theory framework that demonstrates where they fit within the leadership theory body of knowledge. This literature review was an integral part of the preparation for a mixed-methods study related to leadership in the aged care sector which has successfully concluded and one of the major findings of that yet unpublished study is that the followership is positively influenced in their work performance with a reduced turnover intention if they considered that their leader was authentic and ethical.  Authentic and ethical leadership appear to be escalating in importance and translatability to the health and social care environments struggling with unmet workforce demands and high consumer expectations.  The review contains a description and timeline of the development of each of the theories included.  This literature review is useful for investigating either or both leadership theories or their application to health and social care or designing leadership training programs or leader performance assessment tools.